2010
DOI: 10.1111/j.1600-0714.2009.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of bone marrow‐derived mesenchymal stem cells in treating formocresol induced oral ulcers in dogs

Abstract: J Oral Pathol Med (2010) 39: 281–289 Background:  Mesenchymal stem cells (MSCs), a subpopulation of adult somatic stem cells, are an attractive stem cell source in regenerative medicine because of their multipotentiality. In this study, the effects of MSCs transplantation on oral ulcer healing were examined. Methods:  Mesenchymal stem cells were isolated from bone marrow aspirates of dogs by dish adherence and expanded in culture. Oral ulcers were induced by topical application of formocresol in the oral cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Following transfection the cells were incubated at 37°C in humidified air (5% CO2) for 2 h. The transfection medium was then removed and the cells were incubated for an additional 48 h in complete medium (2 ml per well). For imaging GFP autofluorescence of MSCs, unstained slides were directly analysed and green autofluoresence detected by inverted fluorescence microscopy (Leica DM IRB, Leica, Wetzlar, Germany) (15,16).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Following transfection the cells were incubated at 37°C in humidified air (5% CO2) for 2 h. The transfection medium was then removed and the cells were incubated for an additional 48 h in complete medium (2 ml per well). For imaging GFP autofluorescence of MSCs, unstained slides were directly analysed and green autofluoresence detected by inverted fluorescence microscopy (Leica DM IRB, Leica, Wetzlar, Germany) (15,16).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…There was increased expression of both collagen and VEGF (vascular endothelial growth factor) genes in MSCs-treated ulcers compared with controls. [ 17 ] Similar results were seen by Aziz Aly et al . in a study on formocresol induced oral ulcers in dogs using BM and adipose-derived stem cells.…”
Section: Stem Cell Therapy In Oral Mucosal Lesionssupporting
confidence: 84%
“…Some studies have shown that MSCs could also achieve the biological effects by secreting VEGF. VEGF secreted by MSCs has been used in gastric ulcer and oral ulcer healing (El-Menoufy et al 2010;Hayashi et al 2008), in murine ischemic limbs leading to an increase in vessel density (Hoffmann et al 2010), in inhibiting the apoptosis of lung cells (Zhen et al 2010), in facilitating neurological function (Deng et al 2010), enhancing the repair and regeneration of critical sized bone defects (Kanczler et al 2010) and improving cardiac function in failing rat hearts (Tao et al 2009). Therefore, the VEGF 165 gene is the best target gene in gene therapy for promoting angiogenesis.…”
Section: Discussionmentioning
confidence: 99%